Online tutorial and test for system analysis and design / Muthukumaran Raman - Muthukumaran , Raman (2003)
Online Tutorial and Test for System Analysis and Design is a system that is being created to simplify lecturer and students work towards producing better performance and time management. Besides that, this system also will help the students and the lecturer in many ways to overcome the problems that they are facing in current method. This is a Web based system and the system comes with one language that is in English. This system use ASP.NET for its server side scripting and VB.NET for its client side scripting. The systems database is QL Server 2000. Besides that, Macromedia Dream weaver UltraDev tools are used to simplify the creation of this system. This system is being created for the paper System Analysis and Design in Faculty of Computer Science and Information Technology (FCSIT) in University Malaya. This system comes with the features such as online information, lecture notes, getting tutorial and test question; submit tutorial and test answers, tutorial and test submission conformation and marks for tutorial and test. This system also has the features to generate and modify the student's performance graph according to their marks. This system has the capability to be improved in the future with other additional features such ns online discussion, news group, supports many papers and another language that is in Bahasa Malaysia.